Building Systemwide Improvement Capability: Does an Organization's Strategy for Quality Improvement Matter?. Issue 2 (April 2016) - Babich, Lauren P.; Charns, Martin P.; McIntosh, Nathalie; Lerner, Barbara; Burgess, James F.; Stolzmann, Kelly L.; VanDeusen Lukas, Carol
Abstract : Objectives: Health care organizations have used different strategies to implement quality improvement (QI) programs but with only mixed success in implementing and spreading QI organization-wide. This suggests that certain organizational strategies may be more successful than others in developing an organization's improvement capability. To investigate this, our study examined how the primary focus of grant-funded QI efforts relates to (1) key measures of grant success and (2) organization-level measures of success in QI and organizational learning. Methods: Using a mixed-methods design, we conducted one-way analyses of variance to relate Veterans Affairs administrative survey data to data collected as part of a 3.5-year evaluation of 29 health care organization grant recipients. We then analyzed qualitative evidence from the evaluation to explain our results. Results: We found that hospitals that focused on developing organizational infrastructure to support QI implementation compared with those that focused on training or conducting projects rated highest (at α = .05) on all 4 evaluation measures of grant success and all 3 systemwide survey measures of QI and organizational learning success. Conclusions: This study adds to the literature on developing organizational improvement capability and has practical implications for health care leaders. Focusing on either projects or staff training in isolation has limited value. Organizations are more likely to achieve systemwide transformation of improvement capability if their strategy emphasizes developing or strengthening organizational systems, structures, or processes to support direct improvement efforts.